PENGARUH KONSENTRASI KEPEMILIKAN, KECUKUPAN MODAL, EFISIENSI BIAYA, DAN UKURAN BANK TERHADAP KREDIT BERMASALAH (Students' Journal of Economic and Management, 2016)
The objective of the study is to examine the effect of Concentration Of Ownership, Capital Adequacy Ratio, Cost Efficiency, and Bank Size to the Non Performing Loan. The research was conducted on banking company that have been listed in the Indonesian Stock Exchange periode 2011-2013.The sampling method using purposive sampling method with the study period of 2011-2013. Using data from 88 companies that meet the selection criteria. Relationship and influence between the variables described by using multiple regression analysis. The result show that concentration of ownership, capital adequacy ratio, cost efficiency, and bank size are simultan to the non performing loan. concentration of ownership, cost efficiency, and bank size have negatif and significant to the non performing loan,  but capital adequacy ratio has negatif and nof significant to the non performing loan. KEYWORDS : Concentration of Ownership, Capital Adequacy Ratio, Cost Efficiency, Bank Size, and Non Performing Loan